Serum 25-hydroxyvitamin D levels are associated with functional capacity but not with postural balance in osteoporotic postmenopausal women - Brech, Guilherme Carlos (2017)
OBJECTIVES: In post-menopausal women with osteoporosis, insufficient vitamin D levels decrease calcium fixation in the bones and calcium transport in the sarcoplasmic reticulum, which impairs muscle strength, possibly leading to detrimental consequences for the preservation of functional capacity and postural balance, fall prevention, and fracture risk. The aim of this study was to evaluate the association between vitamin D levels and knee muscle strength, postural balance and functional mobility among postmenopausal women with osteoporosis. METHODS: This cross-sectional study included 63 osteoporotic older women (aged 60.6±3.1 years). The subjects completed the Timed Up and Go Test to measure functional mobility, and postural balance was assessed on the AccuSway Plus portable force platform. Maximal strength was tested using an isokinetic dynamometer for knee flexion and extension. The subjects were assessed as a group and were divided into quartiles according to their vitamin D levels. Clinicaltrials.gov: NCT02771834. RESULTS: Vitamin D status was independently associated with the normalized peak torque of the knee extensors (β=0.59; p=0.04) and Timed Up and Go Test (β=-0.07; p<0.001). No between-group differences were observed in the demographic and clinical variables or postural balance; however, significant differences were observed in the Timed Up and Go Test, and the group with the highest vitamin D levels exhibited better performance than the group with the lowest vitamin D levels (p<0.001). CONCLUSION: The serum vitamin D levels were independently associated with normalized knee extension strength and functional mobility in postmenopausal women with osteoporosis.